1997
DOI: 10.1076/ceyr.16.4.333.10689
|View full text |Cite
|
Sign up to set email alerts
|

Calcium ATPase activity and membrane structure in clear and cataractous human lenses

Abstract: These findings support the hypothesis that membranes are deranged in cataractous tissue, which should lead to altered levels of calcium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 8 publications
2
51
0
Order By: Relevance
“…Conversely, in human lenses with cataract, Ca 2þ -ATPase activity was reduced by 50% compared to clear lenses (Paterson et al, 1997) although overall expression in cataractous lenses was unchanged. Recently, upregulation of PMCA2 was reported in the epithelia of cataractous lenses, presumably in compensation for increased intracellular Ca 2þ levels (Marian et al, 2008).…”
Section: The Plasma Membrane Ca 2þ -Atpasementioning
confidence: 88%
See 2 more Smart Citations
“…Conversely, in human lenses with cataract, Ca 2þ -ATPase activity was reduced by 50% compared to clear lenses (Paterson et al, 1997) although overall expression in cataractous lenses was unchanged. Recently, upregulation of PMCA2 was reported in the epithelia of cataractous lenses, presumably in compensation for increased intracellular Ca 2þ levels (Marian et al, 2008).…”
Section: The Plasma Membrane Ca 2þ -Atpasementioning
confidence: 88%
“…All 4 PMCA isoforms are expressed in both bovine (Bian et al, 2000) and human (Marian et al, 2007) lens epithelial cells and although multiple splice variants have been identified in other tissues there is, as yet, no evidence that this is the case in the lens (Bian et al, 2000). Early reports indicated Ca 2þ -ATPase activity in both epithelial cells and cortical fibres (Hightower et al, 1980;Borchman et al, 1989), although, more recent studies suggest that expression and activity are limited to the epithelium (Paterson et al, 1997;Marian et al, 2005).…”
Section: The Plasma Membrane Ca 2þ -Atpasementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a PQ type voltage gated calcium channel was detected to be increased in cataract by nearly 5-fold. Calcium is likely to be an important factor in cataract formation since the activity of calcium-ATPase is reduced by 50% in the membranes of lens epithelia isolated from cataractous lenses compared to clear human lenses (Paterson et al, 1997). Oxidative stress has also been demonstrated to have an effect on the activity of calcium transporters in the lens.…”
Section: Gene Expression Profiles Of Human Age-related Cataractsmentioning
confidence: 99%
“…Several forms of cataracts are directly associated with perturbations in the levels of calcium within the lens, indicating a potential role for the calcium dependent cysteine proteases known as calpains (15)(16)(17). Numerous reports have described the use of a general cysteine protease inhibitor, E-64, in experimental studies of cataract formation.…”
mentioning
confidence: 99%